2021
DOI: 10.47352/jmans.v1i2.85
|View full text |Cite
|
Sign up to set email alerts
|

Biomass and Carbon Stock Variation along slopes in Tropical Forest of Nepal: A case of Depard Community Forest, Makwanpur, Nepal

Abstract: This study was conducted to assess biomass and carbon stock along slopes in Depard community forest, Manahari-6, Makwanpur district of Nepal. In Nepal, carbon stock estimation has been less practiced in community forest. A random sampling method was applied in this study to collect biophysical data i.e. DBH and height by non-destructive method to estimate the quantity of tree biomass and carbon stock. 21 sample plots with 1% sampling intensity were established within the study area. The circular area of 250 m2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 67 publications
1
8
1
Order By: Relevance
“…Several other researchers (Shrestha & Singh, 2008;Mwakisunga & Majule, 2012;Gautam & Mandal, 2016;Bohara et al, 2021) have claimed that higher plant biomass is due to increase in tree density, which is in contrast with the findings of our study. We found that the aboveground biomass varied among the sites due to differences in plant species and community structure.…”
Section: Plant Biomass and Carbon Stockcontrasting
confidence: 99%
“…Several other researchers (Shrestha & Singh, 2008;Mwakisunga & Majule, 2012;Gautam & Mandal, 2016;Bohara et al, 2021) have claimed that higher plant biomass is due to increase in tree density, which is in contrast with the findings of our study. We found that the aboveground biomass varied among the sites due to differences in plant species and community structure.…”
Section: Plant Biomass and Carbon Stockcontrasting
confidence: 99%
“…[20]. Similarly, the biomass and carbon stock in Depard community forest, Manahari-6, Makwanpur district of Nepal were 563.12 tons ha-1 and 242.42 tons ha-1, respectively [21]. Hence, it can be inferred from this study that the expansion of forests has the capacity to mitigate regional and global atmospheric carbon emissions.…”
Section: Resultsmentioning
confidence: 52%
“…Agro-forestry practices, grazing management, restoration of degraded land, mixing fertilizers, and inclusion of grass species are the best strategies for carbon storage under the fodder production system (Prasad et al, 2018). Also, the differences in aboveground carbon stock in the two CFs might be due to variations in forest age, plant species, and local factors (Bohara et al, 2021). The proper management activities lead to more effective stand productivity, and greater increment and assemblage of biomass (Jati, 2012).…”
Section: Discussionmentioning
confidence: 99%